2008
DOI: 10.1097/hjh.0b013e3282f4836d
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hypertension in school children

Abstract: teristics, loose matching and inappropriate statistical methods challenge the interpretation of the study results, unless the authors provide additional explanations. References1 Mosso LM, Carvajal CA, Maiz A, Ortiz EH, Castillo CR, Artigas RA, et al.A possible association between primary aldosteronism and a lower beta-cell function.References 1 Mosso LM, Carvajal CA, Maiz A, Ortiz EH, Castillo CR, Artigas RA, Fardella CE. A possible association between primary aldosteronism and a lower betacell function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 3 publications
(3 reference statements)
2
2
0
Order By: Relevance
“…Because repeated observations were obtained at 3-or 4-year intervals, any habituation is expected to be minimal. 39 Moreover, the same trends over time were found in children of the lowest grade (kindergarten), who had only 1 BP measurement session, compared with older children who could have several BP measurement sessions. Finally, we used US reference data 30 to define elevated BP.…”
Section: Discussionsupporting
confidence: 53%
“…Because repeated observations were obtained at 3-or 4-year intervals, any habituation is expected to be minimal. 39 Moreover, the same trends over time were found in children of the lowest grade (kindergarten), who had only 1 BP measurement session, compared with older children who could have several BP measurement sessions. Finally, we used US reference data 30 to define elevated BP.…”
Section: Discussionsupporting
confidence: 53%
“…Until 2017, the 95th percentile of the sex and age sample was used as the threshold of elevated BP in the pediatric population, i.e., the proportion of children with elevated BP was presumed to be ~5%. Roughly the same values were reported in 1982 in Croatia (945 boys and 980 girls aged 6-17 years) -3.1% for sBP and 2.9% for the dBP, [18] in [2005][2006] in Switzerland (2621 boys, 2586 girls, mean age 12.3±0.5 years) -2.2%, [19] in 2003-2008 in Russia (1300 grade 8-11 students, 14-17 years) -3.7%. [20] At the same time, pediatricians were very reluctant to diagnose "hypertension" in children and insisted on prolonged observation, repeated measurements, and the search for clinical signs characteristic of hypertension in adults.…”
Section: Discussionsupporting
confidence: 82%
“…[20] At the same time, pediatricians were very reluctant to diagnose "hypertension" in children and insisted on prolonged observation, repeated measurements, and the search for clinical signs characteristic of hypertension in adults. [18,19] In 2017, the thresholds of normal BP were more strictly defined for both adults and children. Thus, according to the new recommendations of specialized European and American professional communities, [14,15] the boundary between normal and elevated BP in children remained at the 90th percentile of the parameter distribution in the corresponding sex and age sample, while the boundary between elevated BP and hypertension is the 95th percentile.…”
Section: Discussionmentioning
confidence: 99%
“…Observational surveys have demonstrated that high BP levels are frequently associated with other concomitant CV risk factors, including obesity, dyslipidemia, metabolic syndrome, and diabetes in young individuals 1518. This clustering of multiple, concomitant CV risk factors may exert different effects according to target populations: while in adulthood it raises the susceptibility for developing major CV and renal events, including acute myocardial infarction, stroke, and heart and renal failure,19,20 in childhood it may substantially promote an acceleration of the risk of developing established CV disease in adult age 21,22.…”
Section: Introductionmentioning
confidence: 99%